Pengembangan Media Pembelajaran Interaktif di Sekolah Dasar dalam Pembelajaran PPKn dan Melihat Respon Siswa terhadap Media yang Dikembangkan dalam Media Power Point - Mudaim, Ratu Alit Syarifah (Asian Journal of Early Childhood and Elementary Education, 2024)
It is know that one of the factors that can influence the nation’s progress is the quality of human resources or human resources, imcluding mastering knowledge and technology in the era of the industrial revolution 4.0. in this day and age, the quality of education is increasingly being demanded to improve even more, this is because it can keep up with the current developments of the times which are currently developing very rapidly. Nowadays, learning media is an indispensable basis for the success of the learning process. This research aims to be able to develop interactive learning media assisted by Microsoft PowerPoint. Where this learning media was created using the canva application, about the Pancasila Prinsiples and Pancasila values as the basis of the state in everyday life, for elementary school students and see the response students towards the learning media developed. This research was developed based on the R&D stages of the AIDDE model. The subjects in this research were class IV students.